2009
DOI: 10.1007/s11433-009-0213-z
|View full text |Cite
|
Sign up to set email alerts
|

The relativistic consistent angular-momentum projected shell model study of the N=Z nucleus 52Fe

Abstract: The relativistic consistent angular-momentum projected shell model (ReCAPS) is used in the study of the structure and electromagnetic transitions of the low-lying states in the N =Z nucleus 52 Fe. The model calculations show a reasonably good agreement with the data. The backbending at 12 + is reproduced and the energy level structure suggests that neutron-proton interactions play important roles.ReCAPS, relativistic mean field, angular-momentum projection method, 52 Fe, neutron-proton interactionThe nuclear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The CSM-PNC method is also used to study the recently observed high-spin rotational bands in odd-A nuclei 247,249 Cm and 249 Cf [41]. The relativistic consistent angular-momentum projected shell model (ReCAPS) [42,43] is used in the study of the structure and electromagnetic transitions of the low-lying states in the N = Z nucleus 52 Fe [44]. The model calculations show a reasonably good agreement with the data.…”
Section: Structure and Reactions Of Exotic Nucleimentioning
confidence: 99%
“…The CSM-PNC method is also used to study the recently observed high-spin rotational bands in odd-A nuclei 247,249 Cm and 249 Cf [41]. The relativistic consistent angular-momentum projected shell model (ReCAPS) [42,43] is used in the study of the structure and electromagnetic transitions of the low-lying states in the N = Z nucleus 52 Fe [44]. The model calculations show a reasonably good agreement with the data.…”
Section: Structure and Reactions Of Exotic Nucleimentioning
confidence: 99%
“…The structure of nuclei is an important subject in the field of nuclear physics, and many nuclei have been studied in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The interacting boson model (IBM) is an algebraic model used to study collective nuclear motion.…”
Section: Introductionmentioning
confidence: 99%